Aerobic exercise improves cognition and cerebrovascular regulation in older adults. (26th May 2020) - Guadagni, Veronica; Drogos, Lauren L.; Tyndall, Amanda V.; Davenport, Margie H.; Anderson, Todd J.; Eskes, Gail A.; Longman, R. Stewart; Hill, Michael D.; Hogan, David B.; Poulin, Marc J.
Abstract : Objective: To test the hypothesis that aerobic exercise is associated with improvements in cognition and cerebrovascular regulation, we enrolled 206 healthy low-active middle-aged and older adults (mean ± SD age 65.9 ± 6.4 years) in a supervised 6-month aerobic exercise intervention and assessed them before and after the intervention. Methods: The study is a quasi-experimental single group pre/postintervention study. Neuropsychological tests were used to assess cognition before and after the intervention. Transcranial Doppler ultrasound was used to measure cerebral blood flow velocity. Cerebrovascular regulation was assessed at rest, during euoxic hypercapnia, and in response to submaximal exercise. Multiple linear regression was used to examine the association between changes in cognition and changes in cerebrovascular function. Results: The intervention was associated with improvements in some cognitive domains, cardiorespiratory fitness, and cerebrovascular regulation. Changes in executive functions were negatively associated with changes in cerebrovascular resistance index (CVRi) during submaximal exercise (β = −0.205, p = 0.013), while fluency improvements were positively associated with changes in CVRi during hypercapnia (β = 0.106, p = 0.03). Conclusion: The 6-month aerobic exercise intervention was associated with improvements in some cognitive domains and cerebrovascular regulation. Secondary analyses showed a novel association between changes in cognition and changes in cerebrovascular regulation during euoxic hypercapnia and in response to submaximal exercise.